Postoperative Ratio of C-Reactive Protein to Albumin as a Predictive Marker in Patients with Crohn’s Disease Undergoing Bowel Resection - Hangfen Zhao; Huaying Liu; Weilin Qi; Wei Liu; Lingna Ye; Qian Cao; Xiaolong Ge; Wei Zhou; Xianfa Wang (Gastroenterology Research and Practice)
Background. The ratio of C-reactive protein (CRP) to albumin (CAR) has a significant correlation with postoperative complications and acts as a predictor in patients with pancreatic cancer and colorectal cancer. However, whether the CAR can be used to predict complications in Crohn’s disease (CD) patients after surgery has not yet been reported. Methods. A total of 534 CD patients undergoing surgery between 2016 and 2020 were enrolled. The risk factors of postoperative complications were assessed by univariate and multivariate analyses. The cutoff values and the accuracy of diagnosis for the CAR and postoperative CRP levels were examined with receiver operating characteristic (ROC) curves. Results. The rate of postoperative complications was 32.2%. The postoperative CAR (OR 13.200; 95% CI 6.501-26.803; P<0.001) was a significant independent risk factor for complications. Compared with the CRP level on postoperative day 3, the CAR more accurately indicated postoperative complications in CD patients (AUC: 0.699 vs. 0.771; Youden index: 0.361 vs. 0.599). ROC curves showed that the cutoff value for the CAR was 3.25. Patients with a CAR≥3.25 had more complications (P<0.001), a longer postoperative stay (15.5±0.6 d vs. 9.0±0.2 d, P<0.001), and more surgical site infections (48.2% vs. 5.7%, P<0.001) than those with a CAR<3.25. Conclusions. Compared to the CRP level, the CAR can more accurately predict postoperative complications and can act as a predictive marker in CD patients after surgery.